Research on Classroom Interaction Behavior in a Mobile Tablet-based Unit Teaching Setting (International Conference on Computers in Education, 2022)
In February 2022, the Ministry of Education issued the Key Points of the Ministry of Education's Work in 2022, pointing out the importance of implementing educational digitalization strategy. To implement the requirements of China’s policy and newly released discipline curriculum standards, this study developed a mobile tablet-based unit teaching setting and explored its effects on classroom interaction behavior. The research sample comprised 45 middle school students from western China. Combined with the Improved Flanders-type Analysis System, two Chinese course videos were analyzed before and after implementation. Results show that the mobile tablet-based unit teaching setting had positive effects on the quality of teacher-student interaction, student-student interaction, student-technology interaction, and the classroom interaction quality. The conclusions provide practical teaching guidance and references for various subjects’ unit teaching implementation under the context of the educational digitalization transformation.